Morphometrical Evaluation of Corpus Callosum Using Mid-sagittal Brain MRI Images in Patients With Relapsing-Remitting Multiple Sclerosis - Fatemeh Zohrehvand; Mehrdokht Mazdeh; Leili Tapak; Seyed Kamaledin Hadei; Mohammad Bahiraei (Negah Institute for Scientific Communication, 2022)
Introduction: Corpus callosum (CC), an intracranial organ, is located in the midline of the cerebrum, communicating both the right and left hemispheres. CC undergoes morphological changes in Multiple Sclerosis (MS). The morphometrical changes of organs are directly associated with geographical regions; thus, this study aimed to investigate the morphological alteration of CC in patients with relapsing-remitting MS in Hamadan (Iran) in a retrospective study from April 2011 to April 2021. Methods: Following inclusion and exclusion criteria, 54 and 128 Brain MRI images of RRMS patients and healthy individuals were examined morphologically using PmsDICOMViewer software. Two main morphological indices of area (mm2) and longitudinal (mm) parameters were examined in midsagittal sections of Brain MRI images, including the area of CC (ACC) and associated segments, length of CC (LCC), and height of CC (HCC). Finally, the data were analyzed by SPSS software, version 19. P<0.05 was considered significant, and data were presented as Mean±SEM.  Results: Following MS onset, total ACC was decreased significantly (P<0.05) in MS patients than in control. Also, the area of rosterum/genu (ARG) and area of anterior half midbody of CC (AAMB) showed significant (P<0.05) incremental and decremental trends, respectively. In other indices, no significant differences were detected (P>0.05).  Conclusion: Morphometrical measurements of CC are associated with MS. By assessing the anterior half of CC in brain MRI images (ARG and AAMB), the diagnosis of MS can occur. Thus, the investigation results can be proposed as criteria for radiological confirmation of MS disease.